2010
DOI: 10.1111/j.1600-048x.2010.04891.x
|View full text |Cite
|
Sign up to set email alerts
|

Do bird captures reflect migration intensity? – Trapping numbers on an Alpine pass compared with radar counts

Abstract: A limitation of standardized mist netting for monitoring migration is caused by the lack of knowledge about the relationship between trapped birds and birds flying aloft. Earlier studies related nocturnal radar counts with trapping data of the following day. In this study, we compared for the first time data gathered simultaneously by radar and mist netting, separately for diurnal and nocturnal migration. Trapping numbers were strongly correlated with migratory intensities measured by radar (r>0.6). A multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…We therefore cannot be sure whether the increase of passage intensity of A. mixta during tail-wind conditions (assuming a general southerly flight direction, based on the results of orientation tests) is limited to ground level or whether passage also intensifies at higher altitudes. In any case, at ringing stations where birds are captured during active migration, songbirds are usually captured in higher numbers when they are facing headwinds (Komenda-Zehnder et al 2010), flying lower in order to minimize the effect of the wind, which is also the case at Pape (M. Briedis, pers. comm.).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore cannot be sure whether the increase of passage intensity of A. mixta during tail-wind conditions (assuming a general southerly flight direction, based on the results of orientation tests) is limited to ground level or whether passage also intensifies at higher altitudes. In any case, at ringing stations where birds are captured during active migration, songbirds are usually captured in higher numbers when they are facing headwinds (Komenda-Zehnder et al 2010), flying lower in order to minimize the effect of the wind, which is also the case at Pape (M. Briedis, pers. comm.).…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative use of mist-net data in this way has been criticized on the basis of the data being too variable for statistical conclusions to be drawn (Remsen and Good 1996), although later studies have shown mist-netting of landbirds to be effective in studies of their migration (Wang and Finch 2002). For example, Komenda-Zehnder et al (2010) compared nocturnal measurements by radar with mist-net captures the next day and found a strong correlation in a similar mountainous environment. We feel confident that the overall number of new captures is a representative index of the total population on the move.…”
Section: Assumptions and Potential Limitations Of The Datamentioning
confidence: 99%
“…) and, especially in alpine areas, high concentrations of migrants can occur at these heights (Bruderer , Komenda‐Zehnder et al . ). According to radar measurements from five locations in Austria, on average 36% (±12.3 sd) of diurnal bird migration occurs within 200 m of ground level (Schmidt et al .…”
mentioning
confidence: 97%
“…A current threat for migrating birds is the proliferation of wind energy production (Drewitt & Langston 2006) and wind farms should be situated at locations that minimize the risk of bird collisions (Drewitt & Langston 2008, Gove et al 2013. The majority of diurnal bird migration occurs at low altitudes, below 200 m above ground level (Bruderer & Liechti 1998, 2004, Gatter 2000, Bruderer et al 2012, Schmidt et al 2016) and, especially in alpine areas, high concentrations of migrants can occur at these heights (Bruderer 1996, Komenda-Zehnder et al 2010. According to radar measurements from five locations in Austria, on average 36% (AE12.3 sd) of diurnal bird migration occurs within 200 m of ground level (Schmidt et al 2016).…”
mentioning
confidence: 99%